Polistes dominula (Hymenoptera: Vespidae) paper wasps detect native grasshoppers using olfactory cues - Moreyra, Sabrina; Lozada, Mariana; Fernandez Arhex, Valeria Cristina; Pietrantuono, Ana Laura (Wiley, 2023)
Polistes dominula is an invasive social wasp that preys on the grasshopper Dichroplus elongatus, which constitutes a potential agricultural pest in Northwest Patagonia. This grasshopper feeds on a wide variety of plants, the ‘Dandelion’ (Taraxacum officinale) being one of the main food resources. In this study, by means of a Y-tube olfactometer, we analysed the use of olfactory cues by P. dominula in the detection of grasshoppers. Specifically, we evaluated the attractiveness of live grasshoppers, their traces (i.e. leaves with herbivory traces + prey faeces or only faeces) and herbivory-free leaves. The results showed that foragers equally chose olfactory cues emitted by grasshoppers and leaves with herbivory traces + faeces and herbivory-free leaves, suggesting that the leaves of the host plant also have an important role in the searching behaviour. The current research is the first to demonstrate that the invasive paper wasp orients its search towards either the presence of grasshopper prey or the volatiles of plant leaves. These findings shed new light on predator-prey interactions mediated by olfactory cues in P. dominula, which may play a biological role as a natural controller of D. elongatus, phytophagous pest in the invaded ecosystems.